Significance of Corticospinal, Associative and Inter-Hemispheric Tracts for the Development of Posttraumatic Hemiparesis - E. L. Pogosbekian; E. V. Sharova; L. M. Fadeeva; M. V. Shtern; E. V. Aleksandrova; N. E. Zakharova; I. N. Pronin (Общая реаниматология)
Motor disorders are among the most common consequences of severe craniocerebral injury (traumatic brain injury — TBI). Deeper insights into pathophysiological mechanisms of these disorders is important both from a theoretical point of view and in terms of improving neurorehabilitation approaches.The aim of the study was to investigate the correlation of right–sided posttraumatic hemiparesis severity with composite characteristics of fractional anisotropy (FA) in the segments of the corpus callosum (CC), corticospinal tract (CST) and the inferior fronto-occipital fasciculus (IFO) at diﬀerent stages of traumatic disease (acute, subacute and long-term periods).Material and methods. Cases of 43 patients with TBI were analyzed (28 men and 15 women aged 13 to 59 years, mean age 28±9 years). Forty patients were diagnosed with severe TBI with diﬀuse axonal damage, three patients had moderate severity TBI. Long-term follow up included continuous clinical and neurological examination with evaluation of patient’s level of consciousness using the CRS-R scale, and the degree of motor deﬁcits in right-sided hemiparesis using a ﬁve-point scale. During three post-TBI periods (up to 1 month, from 1 to 6 months, and from 6 to 12 months), patients were examined using diﬀusion tensor MRI (DTI), tractography and FA. Motor, cortico-spinal tracts and IFO were divided by measurement grid, correlations between FA and scores of right-sided hemiparesis were calculated for each segment.Results. FA correlations (P0.05) with the severity of hemiparesis were established not only for CST motor-speciﬁc segments, but also for some CC and IFO segments. In the early period of TBI signiﬁcant correlations with hemiparesis severity were found not only in the contralateral CST segments, but also in the ipsilateral ones. Signiﬁcant diﬀerences in FA in the related CC and CST segments were found between the groups with good and limited motor recovery: at all stages after TBI, FA was higher in patients with successful recovery.Conclusion. The results of the study provide better insight into pathophysiological mechanisms of post-traumatic motor disorders development, therefore favoring optimization of therapeutic strategies.